Euselachian diversity through the uppermost Cretaceous Hell Creek Formation of Garfield County, Montana, USA, with implications for the Cretaceous-Paleogene mass extinction in freshwater environments. (September 2020) - Wynd, Brenen M.; DeMar, David G.; Wilson, Gregory P.
Abstract: Temporal changes in the diversity of euselachians (e.g., sharks and rays) across the Cretaceous-Paleogene (K-Pg) boundary are not well understood, particularly from freshwater ecosystems. Here, we quantitatively analyze euselachian diversity during the last ca. 2 Ma of the Cretaceous using 1518 teeth from 40 vertebrate microfossil localities within the nonmarine facies of the Hell Creek Formation, northeastern Montana, USA. We identify 10 euselachians including one hybodont, five orectolobiforms, one lamniform, one sclerorhynchiform, and two rajiforms. Among these, two are novel and described herein. Diversity metrics reveal an increase in species richness and heterogeneity from the lower to middle portions of the Hell Creek Formation. Thereafter, diversity remained elevated and stable with no turnover until ~5 m below the K-Pg boundary. Above this horizon, including the last ~50 kyr of the Cretaceous, raw species richnesses dropped precipitously, and all euselachians (except possibly Myledaphus ) went locally extinct across the boundary. Preceding this drop in richness, changes in euselachian community structure occurred, including steady declines in the relative abundances of M. pustulosus . These patterns do not support regression of the Western Interior Seaway as the single proximal cause of euselachian extinctions across the K-Pg boundary. Rather, euselachian local extinctions likely were the result of the multiple environmental perturbations occurring just before (volcanism, climate change) and at the K-Pg boundary (bolide impact). This high-resolution temporal pattern of euselachian diversity adds to those from other local taxa (e.g., mammals, lissamphibians) to present a more complex view of the K-Pg mass extinction of the continental biota.